(untitled) (Bangladesh Pharmaceutical Journal, 2020)
The current study was designed to evaluate the antidiarrheal and analgesic activities of the methanol extract of Bouea oppositifolia (Roxb.) Adelb. leaves through iv vivo studies in Swiss Albino mice. Oral administration of the extract at doses of 200- and 400-mg/kg of body weight demonstrated statistically significant (p < 0.05) antidiarrheal activities in castor oil-induced diarrheal mice. The extracts and standard loperamide alleviated diarrhea by margins of 31.82-, 45.45- and 68.17%, respectively. Potential of the plant extract to effectuate analgesia was ascertained both centrally and peripherally. In tail immersion method for the determination of central analgesic activity, the plant extract at both doses enhanced pain tolerance to maximum extents of 192.76% and 221.09%, respectively, compared to standard morphine (419.57%) after 90 minutes of sample administration. Comparable levels of central analgesia were also observed for both doses of the plant extracts at 30 and 60 minutes of pharmacological intervention and the p value of less than 0.05 illustrated statistical significance of the activity. On a similar note, potent peripheral analgesic activities were observed for both doses of the extract as evident by 45.45- and 54.55% inhibitions of acetic acid induced writhing responses, respectively. Compared to the standard acetylsalicylic acid characterized by 78.18% inhibition, the peripheral analgesic activity of the plant was found to be statistically significant (p < 0.05). The results of the study are indicative of the presence of potentially bioactive phytoconstituents with antidiarrheal and analgesic properties which might lead to newer drug candidates in future. Bangladesh Pharmaceutical Journal 23(2): 167-171, 2020